Managing Drug-resistant Acinetobacter baumannii Infection in Premature Infants - Fu-Ruei Zeng; Chia-Ning Chang; Sheng-Yuan Ho (Journal of Medical Sciences)
Acinetobacter baumannii is a major pathogen in neonatal intensive care units, particularly affecting extremely premature infants and posing challenges due to its extensively drug-resistant (XDR) or pan-drug-resistant (PDR) profiles. This report describes the successful treatment of two extremely premature neonates with severe, XDR/PDR A. baumannii infections using combination therapy of colistin, tigecycline, and cefoperazone/sulbactam. The first case involved a 26-week gestation neonate with ventilator-associated pneumonia unresponsive to initial therapy. The infant was successfully extubated after a tailored regimen. The second case, a 26-week neonate with XDR A. baumannii bacteremia and septic shock, presented with complications including necrotizing enterocolitis. Despite these challenges, the infant recovered fully after the combination therapy, with no long-term sequelae observed. These findings emphasize the potential of combination therapy as a life-saving intervention for critically ill neonates with multidrug-resistant A. baumannii infections, highlighting the need for further research to refine therapeutic strategies in this vulnerable population.